Coordinated path following of multiple underacutated marine surface vehicles along one curve. (September 2016) - Liu, Lu; Wang, Dan; Peng, Zhouhua
Abstract: This paper investigates the coordinated path following problem for a fleet of underactuated marine surface vehicles (MSVs) along one curve. The dedicated control design is divided into two tasks. One is to steer individual underactuated MSV to track the given spatial path, and the other is to force the vehicles dispersed on a parameterized path subject to the constraints of a communication network. Specifically, a robust individual path following controller is developed based on a line-of-sight (LOS) guidance law and a reduced-order extended state observer (ESO). The vehicle sideslip angle due to environmental disturbances can be exactly identified. Then, the vehicle coordination is achieved by a path variable containment approach, under which the path variables are evenly dispersed between two virtual leaders. Another reduced-order ESO is developed to identify the composite disturbance related to the speed of virtual leaders and neighboring vehicles. The proposed coordination design is distributed since the reference speed does not need to be known by all vehicles as a priori . The input-to-state stability of the closed-loop network system is established via cascade theory. Simulation results demonstrate the effectiveness of the proposed design method. Abstract : Highlights: This paper is the first trial to address the coordinated path following problem of multiple underactuated MSVs along one curve. A novel ESO based LOS guidance law is proposed for the path following design, where the time-varying sideslip angle can be accurately identified. A path variable containment design approach is proposed to fulfill the vehicle coordination along one curve such that the vehicles are evenly dispersed.